The role of starting knee angle in squat jump force-velocity profiles: interactions with subjects’ strength levels and imputed push-off distance - Qin, Xuelin; Liu, Beibei; Tang, Ruolin; Liu, Yan; García-Ramos, Amador (Frontiers in Physiology, 2025)
IntroductionThis study investigated whether differences in the force-velocity (F-v) profile obtained using Samozino’s method during squat jumps (SJ) performed at varying knee angles are influenced by subjects’ strength levels and the push-off distance (HpO) used in the analysis.MethodsTwenty-one resistance-trained men were classified as stronger (n = 10) or weaker (n = 11) based on the external load required to achieve a 10 cm SJ height. F-v profiles were randomly assessed over three sessions, with SJs performed at starting knee angles of 70° (SJ70), 90° (SJ90), and 110° (SJ110), using either the actual HpO specific to each condition or a standardized HpO corresponding to SJ90.ResultsSignificant differences between SJ types were observed for maximum force (F0) and the F-v slope (SJ110 > SJ90 > SJ70). These differences were never influenced by subjects’ strength levels. The standardized HpO produced similar outcomes for maximum power (Pmax) and maximum velocity (v0), and more consistent results for F0 and the F-v slope compared to the actual HpO.DiscussionRegardless of strength levels, standardizing HpO at 90° and allowing subjects to select a starting knee angle between 70° and 90° could simplify the evaluation process and improve the comparability of F-v profiles across subjects when using Samozino’s method.